Political Expediencies and the Process of Identity Construction: The Quest for Indian Identity in Malaysia - Anbalakan Kailasam (Kajian Malaysia, 2015)
One way of gauging identity construction in a community is by studying how the community organises itself into associations, the causes these associations fight for and the stands they take on issues pertaining to their communities' interests. The English-educated Indian elite in Malaysia began making efforts in the last quarter of the 19th century to organise themselves into socioeconomic and quasipolitical associations. However, no cohesive ethnic identity was visible even among this English-educated middle class until the mid-forties. The Indians at large remained as fragmented as ever. Ironically, they did not even have a truly national organisation with which they could identify themselves as an ethnic community. This situation began to change with the formation of the Malayan Indian Congress (MIC) in August 1946. The MIC was the first full-fledged political party of the Indian community in Malaysia, and it was formed to defend Indian interests. True to this objective, the MIC played a crucial role in defending the rights of the Indian community during the period soon after the Second World War. With that, the MIC inadvertently paved the way for the transition of Indian identity from being an immigrant community to being rightful citizens of Malaysia. An analysis of the MIC's role in and stance on various issues that affected the community from the time of its inception through the midfifties is imperative for understanding identity construction among Indians in Malaysia. An attempt is made here to study the various phases that the MIC went through during its political struggle as the representative of the Indiancommunity and its influence on the transition of Indian identity from an immigrant community to citizens.